Pithellobium dulce (Roxb.) Benth. Fruit Flour Intake Enhances Short-Chain Fatty Acid Production and Glucose Metabolism in BALB/c Mice - Alba R. Hernández García; Dalia S. Aguilar Ávila; Juan M. Viveros Paredes; Rocío I. López Roa; Alma H. Martínez-Preciado (Polish Journal of Food and Nutrition Sciences)
Pithecellobium dulce (Roxb.) Benth. ( P. dulce ) is a legume native to Mexico with a rich profile of bioactive compounds, including dietary fiber (DF) and phenolics, which have shown potential health benefits. This study investigates the effects of P. dulce fruit flour (PDF) on glucose metabolism and short-chain fatty acid (SCFAs) production in healthy BALB/c mice. Four groups – unmanipulated control (UC), vehicle control (VC), positive control inulin-treated (PC), and PDF-treated – received oral solutions for 60 days. Variables such as body weight and food intake were monitored, glucose and insulin tolerance tests were conducted, SCFAs in cecal contents were analyzed via gas chromatography, besides goblet cells in the descending colon were quantified. PDF in 100 g dry matter contained 57.44 g of carbohydrates and 10.48 g of DF including 7.77 g of insoluble DF and 2.71 g of soluble DF. Total phenolic content of PDF was 526 mg GAE/100 g. PDF consumption significantly improved glycemic regulation, as evidenced by lower blood glucose levels and enhanced glucose clearance in tolerance tests compared to controls. This was accompanied by increased SCFAs production, particularly propionic and butyric acids, associated with improved glucose homeostasis. PDF also promoted intestinal health by significantly increasing goblet cells in the descending colon, indicating enhanced epithelial barrier integrity. These effects were attributed to DF fermentation and phenolic compound activity, which boosted SCFAs production and reduced postprandial glycemia. These findings highlight P. dulce as a promising functional ingredient for improving glycemic control and intestinal health, providing a foundation for future research in metabolic disorders and prebiotic therapies.